The Effect of Logotherapy to Diabetes Mellitus Client’s Meaning of Life - Ah Yusuf; Rr. Dian Tristiana; Leni Anitasari; Ira Suarilah (Faculty of Nursing Universitas Padjadjaran, 2019)
Diabetes mellitus is a chronic disease that caused meaning of life disturbance. Logotherapy is an intervention that could affect people life perspective. The purpose of this study was to analyze the effect of logotherapy implementation to the meaning of life in diabetes mellitus client. This study used quasy-experimental pretest-post-test with control group. The dependent variable was meaning of life, and the independent variable was the implementation of logotherapy. Sample in this study was 30 respondents, were taken by using consecutive sampling. The meaning of life were taken by using Purpose in Life Test (PIL Test) then analyzed by using Wilcoxon Sign Rank Test and Mann Witney U statistic test, a= £0.05. The result showed logotherapy had significant effect on meaning of life in the treatment group (p=0,001). Statistical test Mann Whitney U Test showed that there was a difference meaning of life in control group and the treatment group after implementation of logotherapy. It could be concluded that the implementation of logotherapy has an effect to increasing the meaning of life in diabetes mellitus client. Further study was recommended to developing deeper study that related to logotherapy in diabetes mellitus client.